Actions of noradrenaline on substantia gelatinosa neurones in the rat spinal cord revealed by in vivo patch recording - Sonohata, Motoki (Blackwell Science Inc, 2004)
To elucidate the mechanisms of antinociception mediated by the descending noradrenergic pathway in the spinal cord, the effects of noradrenaline (NA) on noxious synaptic responses of substantia gelatinosa (SG) neurones, and postsynaptic actions of NA were investigated in rats using an in vivo whole-cell patch-clamp technique. Under urethane anaesthesia, the rat was fixed in a stereotaxic apparatus after the lumbar spinal cord was exposed. In the current-clamp mode, pinch stimuli applied to the ipsilateral hindlimb elicited a barrage of EPSPs, some of which initiated an action potential. Perfusion with NA onto the surface of the spinal cord hyperpolarized the membrane (5.0–9.5 mV) and suppressed the action potentials. In the voltage-clamp mode (V(H), −70 mV), the application of NA produced an outward current that was blocked by Cs(+) and GDP-β-S added to the pipette solution and reduced the amplitude of EPSCs evoked by noxious stimuli. Under the blockade of postsynaptic actions of NA, a reduction of the evoked and spontaneous EPSCs of SG neurones was still observed, thus suggesting both pre- and postsynaptic actions of NA. The NA-induced outward currents showed a clear dose dependency (EC(50), 20 μm), and the reversal potential was −88 mV. The outward current was mimicked by an α(2)-adrenoceptor agonist, clonidine, and suppressed by an α(2)-adrenoceptor antagonist, yohimbine, but not by α(1)- and β-antagonists. These findings suggest that NA acts on presynaptic sites to reduce noxious stimuli-induced EPSCs, and on postsynaptic SG neurones to induce an outward current by G-protein-mediated activation of K(+) channels through α(2)-adrenoceptors, thereby producing an antinociceptive effect.